2008
DOI: 10.1093/humrep/den487
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ovarian reserve in adult childhood cancer survivors using anti-Mullerian hormone

Abstract: AMH can be used to identify subgroups of CCS at risk for decreased fertility or premature ovarian failure. In these survivors, options for fertility preservation should be considered prior to starting treatment since they may be at risk for poor chances of pregnancy after assisted reproductive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(48 citation statements)
references
References 36 publications
1
45
0
2
Order By: Relevance
“…In this respect, the value of serum AMH concentration is currently gaining attention for the assessment of fertility. Several studies have evaluated the use of serum AMH concentration to assess ovarian damage in females surviving childhood malignancy [19,20,21,22,23]. The most recent report by Brougham et al [23] showed AMH to be a marker of gonadotoxicity in a prospective study of 22 pre- and postpubertal females treated for cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the value of serum AMH concentration is currently gaining attention for the assessment of fertility. Several studies have evaluated the use of serum AMH concentration to assess ovarian damage in females surviving childhood malignancy [19,20,21,22,23]. The most recent report by Brougham et al [23] showed AMH to be a marker of gonadotoxicity in a prospective study of 22 pre- and postpubertal females treated for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…AMH levels are reduced after chemotherapy and radiotherapy; therefore, AMH is currently considered to be a useful indicator of the long-term impact of chemotherapy on reproduction capacity in adult females [17,18]. Recent reports have examined the use of AMH for the prediction of ovarian reserve in female CCSs [19,20,21,22]. The aim of the present retrospective study was to measure serum AMH concentrations and compare them with those of gonadotropin to evaluate ovarian function in CCSs.…”
Section: Introductionmentioning
confidence: 99%
“…Alkylating agents and abdominal radiotherapy, in particular, can have a deleterious effect on ovarian function (9). To determine ovarian reserve, anti-Mü llerian hormone (AMH) was identified as a reliable serum marker (10).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian reserve, the number of remaining follicles in the ovary, declines naturally with age; however, researchers recently demonstrated that age alone is not an accurate indicator of reproductive age and that other factors may be implicated in the depletion of the ovarian follicle pool (van Disseldorp et al, 2008). Thus, identifying factors that contribute to the decline of ovarian reserve may aid in the prevention and early detection of follicular depletion, premature ovarian failure, and importantly impaired fertility (Lie Fong et al, 2009). …”
Section: Call-outsmentioning
confidence: 99%